#TITLE_ALTERNATIVE# - Sadharma - nIM: 15114070, Rakha
This undergraduate thesis studies the changes of seabed elevation in Patimban area by using a DEM (Digital Elevation Model) of the seabed elevation in the year 2010, 2013, and 2016. The DEM is constructed by using depth data procured from nautical chart no.79 published in 2010, nautical chart no.79 published in 2013, and bathymetric survey report that was conducted in 2016. These depth data have different reference plane where the 2010 and 2013 data is defined from the chart datum while the 2016 data is defined from the mean sea level. These depths are referenced to the chart datum, which is 0.6 meters below the mean sea level. Volume change value is the result of calculating the differences in depth values between data from different epochs. The uncertainty of the model is assessed to know how reliable the DEM can represent the changes of seabed elevation. Uncertainty assessment for the model is done by using RMSE (Root Mean Square Error) for the DEM of each epoch and calculating the uncertainty propagation for the volume calculation process. The resulting model shows that the area experiences sedimentation with a magnitude of 183 × 106 m3 and an annual rate of 30 × 106 m3/year. The uncertainty of the volume change calculation is within a factor of 1.9.